Functional properties of GABAA receptors of AII amacrine cells of the rat retina - Beltrán-Matas, Pablo; Hartveit, Espen; Veruki, Margaret L. (Frontiers in Ophthalmology, 2023)
Amacrine cells are a highly diverse group of inhibitory retinal interneurons that sculpt the responses of bipolar cells, ganglion cells, and other amacrine cells. They integrate excitatory inputs from bipolar cells and inhibitory inputs from other amacrine cells, but for most amacrine cells, little is known about the specificity and functional properties of their inhibitory inputs. Here, we have investigated GABAA receptors of the AII amacrine, a critical neuron in the rod pathway microcircuit, using patch-clamp recording in rat retinal slices. Puffer application of GABA evoked robust responses, but, surprisingly, spontaneous GABAA receptor-mediated postsynaptic currents were not observed, neither under control conditions nor following application of high-K+ solution to facilitate release. To investigate the biophysical and pharmacological properties of GABAA receptors in AIIs, we therefore used nucleated patches and a fast application system. Both brief and long pulses of GABA (3 mM) evoked GABAA receptor-mediated currents with slow, multi-exponential decay kinetics. The average weighted time constant (τw) of deactivation was ~163 ms. Desensitization was even slower, with τw ~330 ms. Non-stationary noise analysis of patch responses and directly observed channel gating yielded a single-channel conductance of ~23 pS. Pharmacological investigation suggested the presence of α2 and/or α3 subunits, as well as the γ2 subunit. Such subunit combinations are typical of GABAA receptors with slow kinetics. If synaptic GABAA receptors of AII amacrines have similar functional properties, the slow deactivation and desensitization kinetics will facilitate temporal summation of GABAergic inputs, allowing effective summation and synaptic integration to occur even for relatively low frequencies of inhibitory inputs.